2008
DOI: 10.1080/13693780802078180
|View full text |Cite
|
Sign up to set email alerts
|

A case of endocarditis caused by the yeastPichia fabianiiwith biofilm production and developedin vitroresistance to azoles in the course of antifungal treatment

Abstract: Pichia fabianii, a yeast rarely causing human infections, was isolated from the blood of a patient with aortic valve endocarditis. The isolates were initially identified biochemically as Candida pelliculosa, but based on direct sequencing of the ITS2 region of rRNA, they were subsequently reidentified as P. fabianii. Antifungal therapy with fluconazole and later with voriconazole led to the development of resistant variants which had high MIC values to both antifungals. Strong biofilm formation by this yeast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 20 publications
(17 reference statements)
2
35
1
2
Order By: Relevance
“…As commercial yeast identification and diagnostic kits (e.g. API 20C AUX, ID32C and Vitek 2) used in routine practice have a limited ability to identify Cyberlindnera fabianii, this organism has also been misidentified as Pichia anomala or Candida utilis in other studies (Gabriel et al, 2012;Grenouillet et al, 2010;Hamal et al, 2008;Valenza et al, 2006). Yun et al (2013) described a case of L. fabianii from the blood culture of a 47-year-old woman, which was identified initially as C. utilis by Vitek 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As commercial yeast identification and diagnostic kits (e.g. API 20C AUX, ID32C and Vitek 2) used in routine practice have a limited ability to identify Cyberlindnera fabianii, this organism has also been misidentified as Pichia anomala or Candida utilis in other studies (Gabriel et al, 2012;Grenouillet et al, 2010;Hamal et al, 2008;Valenza et al, 2006). Yun et al (2013) described a case of L. fabianii from the blood culture of a 47-year-old woman, which was identified initially as C. utilis by Vitek 2.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, in earlier cases, isolation of C. fabianii has only been reported from blood specimens and only infrequently. A review of the literature showed only seven case reports of fungaemia caused by P. fabianii worldwide: three from neonates (Bhally et al, 2006;Grenouillet et al, 2010;Wu et al, 2013) and four from adult patients (Gabriel et al, 2012;Hamal et al, 2008;Valenza et al, 2006;Yun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Such antifungal resistance may be facilitated by the ability of this species to form biofilms [4]. In addition, commercial biochemical fungal identification kits often misidentify C. fabianii as Candida utilis [3,5]. Here, we report a case of fungemia caused by C.…”
Section: Introductionmentioning
confidence: 92%
“…However, C. utilis fungemia is rare and there are reported cases of species misidentification using the VITEK-2 YST ID card [3,5]. In particular, unusual species such as C. fabianii are not included in the databases of commercial kits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation